1995
DOI: 10.1177/036354659502300304
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart Procedure: Two- to Five-Year Followup With Clinical Correlation to Severity of Glenoid Labral Lesion

Abstract: We report our results using the arthroscopic Bankart technique described by Morgan (transglenoid suture) on 60 consecutive patients with anterior instability. All had detachment of the glenoid labrum at surgery. Forty-seven patients were available for final followup, which ranged from 2 to 5 years. Of these patients, 18 had experienced recurrent dislocation and 3 had experienced episodes of subluxation after surgery, for an overall failure rate of 42%. Partway into the study, we began to correlate severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 20 publications
1
39
0
7
Order By: Relevance
“…Abnormalities commonly encountered at re-exploration after failed arthroscopic or open repair include an unhealed Bankart lesion, 77,81 humeral avulsion of the glenohumeral ligaments, 82,83 extensive glenoid erosion or deficiency from a bony Bankart lesion, 38,84,85 excessive capsular laxity, 81,86 a defect of the rotator interval, 87 an engaging Hill-Sachs lesion 38,39 and reduced retroversion of the head of the humerus or excessive retroversion of the glenoid cavity. 88 Several additional factors have been associated with recurrent instability after arthroscopic stabilisation including a younger age at surgery, 59,89 non-compliance with post-operative immobilisation, 84,90 early return to contact sport, 86,91 absence or deficiency of the capsulolabral complex and poor inferior glenohumeral ligaments, 86,92 and multiple episodes of instability before stabilisation. 80,93 The wide variation in the rates of recurrence after arthroscopic stabilisation may also be a reflection of the inherent technical difficulty in performing these procedures.…”
Section: Factors Associated With Recurrent Instability After Surgicalmentioning
confidence: 99%
“…Abnormalities commonly encountered at re-exploration after failed arthroscopic or open repair include an unhealed Bankart lesion, 77,81 humeral avulsion of the glenohumeral ligaments, 82,83 extensive glenoid erosion or deficiency from a bony Bankart lesion, 38,84,85 excessive capsular laxity, 81,86 a defect of the rotator interval, 87 an engaging Hill-Sachs lesion 38,39 and reduced retroversion of the head of the humerus or excessive retroversion of the glenoid cavity. 88 Several additional factors have been associated with recurrent instability after arthroscopic stabilisation including a younger age at surgery, 59,89 non-compliance with post-operative immobilisation, 84,90 early return to contact sport, 86,91 absence or deficiency of the capsulolabral complex and poor inferior glenohumeral ligaments, 86,92 and multiple episodes of instability before stabilisation. 80,93 The wide variation in the rates of recurrence after arthroscopic stabilisation may also be a reflection of the inherent technical difficulty in performing these procedures.…”
Section: Factors Associated With Recurrent Instability After Surgicalmentioning
confidence: 99%
“…Green and Christensen operated on 60 patients with a follow-up of 40 months and reported a relapse rate of 42%. There was inferior glenohumeral ligament insufficiency in the relapsing cases [10]. In these procedures capsular volume increase is not repaired, which probably is related to the unfavourable results.…”
Section: Discussionmentioning
confidence: 96%
“…Arthroscopic capsulorrhaphy with staples presented a high rate of complications and lack of success (17)(18)(19) . Transglenoid arthroscopic suture presented variable results (20)(21)(22)(23)(24)(25) . Usually, this technique presents results that are inferior to open Bankart repair, although Savoie et al (24) reported achieving acceptable results with this technique.…”
Section: Discussionmentioning
confidence: 99%